Sigo, logo invisto! : o papel dos influenciadores de mídias sociais na participação de seus seguidores no mercado de ações - Duarte, Patrick Mauricio (2022)
The power social media influencers (SMI) exert over their audiences has seen increasing emphasis in influence marketing (IM). Nonetheless, a variation of this context apparently has not been explored by academia and has only gained traction in institutional publications. This is the case for the impact personal finance influencers (PFI) - digital influencers who produce financially-related content - have on the capacity to mold attitudes and behaviors towards financial decisions, consumption habits, spending control, and investment choices. In light of this, the present study aims to analyze the role that personal finance influencers play among their followers in the intention and participation in the stock market. The Theory of Planned Behavior (TPB) is used as the theoretical lens and, additionally, the effect Parasocial Relations (PSR) have on influencers and their followers is analyzed. Primary data collection was done using an online survey responded by 87 individuals who characterized themselves as following a social media influencer and being active in the stock market. In the next phase, data were analyzed through techniques related to structural equation modeling (SEM). The model's hypotheses were tested by deploying the partial least squares (PLS-SEM) method using SmartPLS 3.0 software. Results confirm that the TPB model is adequate for understanding PFI followers' intentions and behaviors with respect to participating in the stock market. Attitude towards participation in the stock market, subjective norm, and behavioral control predicted behavioral intention. Attitude gained higher prediction power over intention when the PSR construct was included revealing its indirect effect, as previously observed in prior research. In conclusion, the Parasocial Relationship between followers and influencers can lead to changes in attitudes, opinions, and behaviors among followers.